Association between nutrient intake and telomere length in Japanese female university students. (17th February 2021) - Mizuno, Yuki; Konishi, Shoko; Goto, Chiho; Yoshinaga, Jun; Hidaka, Mikie; Imai, Hideki
Abstract: Objective: Telomere length can be a biomarker of cumulative oxidative stress and inflammation indicating biological aging. Previous studies examined association of nutrient intake with telomere length targeting middle-aged and elderly individuals. This study examined whether dietary macro- and micronutrient intake was associated with telomere length in young females. Methods: Seventy-four Japanese young females (median (interquartile range) age was 19 (19 − 20) years) participated. We estimated their intake of nutrients (energy, protein, fat, carbohydrate, essential elements, vitamins, fatty acids, and dietary fibre) using a semi-quantitative food frequency questionnaire and measured telomere length (T/S ratio, the ratio of telomere repeat copy number (T) to single-copy gene number (S)) of DNA extracted from blood by qPCR. The association between telomere length and tertiles of nutrient intake were analysed. Results: The median (interquartile range) of telomere length was 0.70 (0.52 − 0.98). Vitamin A intake was positively associated with telomere length (tertile 1 vs. 2, coefficient [95% confidence interval] = 0.42 [0.12, 0.71]; tertile 1 vs. 3, coefficient [95% confidence interval] = 0.33 [0.04, 0.62]) after adjusting for covariates (age, BMI, passive smoking, and drinking). Conclusions: Our findings suggest that variation in vitamin A intake might influence telomere attrition in healthy individuals.